2007
DOI: 10.1002/marc.200790018
|View full text |Cite
|
Sign up to set email alerts
|

Macromol. Rapid Commun. 9/2007

Abstract: Cover: The cover picture describes a new approach which enables controllable formation of nano polymer particles. The resultant particles could contain only one or two polymer chains, i.e. they are molecular bricks with potential important applications. Further details can be found in the article by C. Norakankorn, Q. Pan,* G. L. Rempel,* and S. Kiatkamjornwong on page 1029.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
3
9
0
Order By: Relevance
“…These results were also consistent with other work which reported that AIBN was a suitable initiator for emulsion or microemulsion polymerization and more economical than the system using a water soluble initiator 22. For the emulsion polymerization of methacrylate monomers such as 2‐hydroxyethyl methacrylate (HEMA), methyl methacrylate (MMA), and butyl methacrylate (BMA), more hydrophobic monomers, the hydrophobic initiators lead to much better polymerization results, with much less coagulum and smaller particles, than the hydrophilic potassium peroxodisulfate 23.…”
Section: Resultssupporting
confidence: 93%
“…These results were also consistent with other work which reported that AIBN was a suitable initiator for emulsion or microemulsion polymerization and more economical than the system using a water soluble initiator 22. For the emulsion polymerization of methacrylate monomers such as 2‐hydroxyethyl methacrylate (HEMA), methyl methacrylate (MMA), and butyl methacrylate (BMA), more hydrophobic monomers, the hydrophobic initiators lead to much better polymerization results, with much less coagulum and smaller particles, than the hydrophilic potassium peroxodisulfate 23.…”
Section: Resultssupporting
confidence: 93%
“…The particle size of nanosized PIP decreased with increasing surfactant concentration. The results were similar to those obtained in the preparation of poly(MMA) nanoparticles initiated by AIBN via differential microemulsion polymerization . For the preparation of nanosized PIP with a particle size of around 20 nm, the required surfactant amount could be as low as 0.09 of the isoprene monomer amount by weight.…”
Section: Resultssupporting
confidence: 84%
“…Monodisperse PMMA nanospheres 53 were synthesized by surfactant-free microemulsion polymerization with potassium peroxodisulfate as initiator. 17,65 The monomer and the initiator concentrations were adjusted to obtain nanoparticles with an average size in the order of 300 nm.…”
Section: B Pmma Fluorescent Nanospheresmentioning
confidence: 99%
“…In this article, we present an optical technique that allows the direct measurement of the absolute quantum yield of fluorescent nanoparticles such as zeolite L ͑ZL͒ nanocrystals 2,[20][21][22][28][29][30][31] and poly͑methyl methacrylate͒ ͑PMMA͒ nanospheres 5,17,19,[23][24][25]53,54 both loaded with fluorescent perylene molecules, which are well known for their chemical and photochemical stabilities as well as for their high quantum yield. 5,55 Our experimental method is based on the measurement of the diffuse reflectance ͑DR͒ spectra of fluorescent nanopigments adsorbed on microcrystalline cellulose substrates.…”
Section: Introductionmentioning
confidence: 99%